1676b The management of psychosocial risks 9 years after the implementation of the european framework agreement on work-related stress in italy: a monitoring study. (24th April 2018) - Di Tecco, C; Ronchetti, M; Persechino, B; Ghelli, M; Iavicoli, S
Abstract : In 2008, Italy implemented the 2004 European Framework Agreement on work-related stress into the national legal framework on health and safety at work (L.D. 81/08). Then, the Department of Occupational and Environmental Medicine, Epidemiology and Hygiene, currently part of the Italian Workers Compensation Authority (INAIL), offered to companies a methodology for the assessment and management of risks associated with work-related stress as a participative proposal based on an evidence-based approach and validated tools. The INAILs methodology comes from the adaptation of the HSE's Management Standards approach and integrates findings of the most prominent national existing experiences and the legal requirements as well. INAIL offered also a web platform, consisting of an operational web interface where companies can have free access to the online tools and find useful documentation to support companies with a web interface as well as to create a structured repository where assessment data from companies are constantly collected. The INAIL methodology resulted in being the most used methodology by Italian companies and data collected through the web platform were useful in the view of optimising and standardising the tools over time. Recent findings showed the state of art of Italian enterprises in managing psychosocial risks resulting from a project financed by the Ministry of Health, involving INAIL as principal investigators, regional prevention units and two universities. This project aimed to offer a monitoring and intervention plan for the optimisation of the assessment and management of psychosocial risks at work in the view of contributing to the evaluation of the policy interventions' effectiveness. A further study showed the growing level of awareness and the impact of policies on psychosocial risks and work-related stress in Italy using EU-OSHA's European survey of enterprises on new and emerging risks (ESENER) data. Italian companies have shown a radical change in the management of psychosocial risks overtime and Italy has gone from being a country not prioritising these risks enough to one of the most active European countries in this area.